Impact of alternative healthcare plans on out-of-hours help-seeking intentions in Switzerland (Swiss Medical Weekly, 2018)
INTRODUCTION In Switzerland, mandatory health insurance plans (standard) offer free access to secondary and emergency care. However, in return for a lower premium, individuals can choose alternative healthcare plans (HCPs), with either a general practitioner (GP) or a medical call centre (Telmed) acting as gatekeeper. AIM To examine the impact of alternative HCPs on patients’ intended help-seeking behaviour out-of-hours (OOH) in Switzerland. METHODS A secondary analysis of the Swiss data collected for the EurOOHnet survey on help-seeking behaviour in Denmark, the Netherlands and Switzerland was made. The survey used hypothetical scenarios for measuring two outcome measures: intended help-seeking for (1) OOH care and (2) OOH face-to-face care. Binomial regression analyses were used to test the influence of HCPs on intended OOH help-seeking, adjusted for other (population) characteristics. RESULTS Telmed-insured persons were more inclined to OOH help-seeking than persons with a standard HCP (odds ratio [OR] 2.28, 95% confidence interval [CI] 1.91–2.72; controlled for other population factors), mainly driven by contact with the medical call centre (31 vs 5%), and were less inclined to have an OOH face-to-face contact (OR 0.69, 95% CI 0.55–0.87). Persons with a GP HCP had a lower intended use of face-to-face OOH care contacts than persons with a standard plan (OR 0.74, 95% CI 0.63–0.86). CONCLUSION Alternative HCPs on a voluntary basis seem to influence the use of OOH care. These results could be relevant for policy makers, especially from non-gatekeeping countries, to reduce irrelevant use and subsequent costs of emergency and OOH care services.